Protection of ascorbic acid from copper(II)-catalyzed oxidative degradation in the presence of flavonoids: quercetin, catechin and morin - Beker, Bilge Yildogan; Sonmezoglu, Inci; Imer, Filiz; Apak, Resat (TAYLOR & FRANCIS LTD, 2011)
Protection of ascorbic acid (AA) (vitamin C) from Cu(II)-catalyzed autoxidation is an important aspect of antioxidant chemistry. The autoxidation of AA in the absence and presence of Cu(II) ions was investigated in aerated solution at room temperature and I = 0.1 ionic strength (KNO3); the effects of three different flavonoids of similar structure (quercetin, morin and catechin) and their mixtures on the AA system were studied. The concentration of unoxidized AA remaining in solution was measured with the modified cupric ion reducing antioxidant capacity spectrophotometric method. The Cu(II)-catalyzed oxidation at pH 4.5 followed first-order kinetics with respect to AA concentration. Catalytic autoxidation of AA was inhibited to a greater extent by stable quercetin and morin complexes of Cu(II) than by catechin complex. The inhibitive effectiveness order of mixtures gives information about possible synergistic or antagonistic combinations of flavonoid antioxidants, which should be further confirmed with other antioxidant tests.
Keywords: Ascorbic acid; vitamin C; autoxidation; copper(II) catalysis; flavonoids; antioxidant protection; CHELATE CATALYZED OXIDATION; ANTIOXIDANT ACTIVITY; COPPER IONS; SPECTROPHOTOMETRIC DETERMINATION; MOLECULAR-OXYGEN; METAL-ION; KINETICS; IRON; COMPLEXATION; Food Science & Technology; Nutrition & Dietetics